Synthesis and studies of cyclen based lanthanide complexes for the detection of ions and molecules and the hydrolysis of phosphodiesters - Harte, Andrew (Trinity College (Dublin, Ireland). School of Chemistry, 2005)
This thesis entitled "Cyclen Based Lanthanide Complexes for the Detection of Ions and Molecules and the Hydrolysis of Phosphodiesters" is divided into five chapters. Chapter 1, the introduction, is divided into two parts. The first half introduces the principles of luminescent sensing before illustrating some examples of fluorescent sensors. Then the advantages of lanthanide luminescent signalling systems are discussed followed by a description of the mechanism by which lanthanide luminescence is produced. Finally, a review of various lanthanide luminescent chemosensors is presented. The second half of the introduction deals with the area of phosphodiester hydrolysis. It shall begin by looking at natural ribonucleases capable of hydrolysing RNA, followed by a look at the mechanism of hydrolysis. The use of metal ions to promote phosphodiester hydrolysis is then discussed, followed by a discussion on the use of metal complexes.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin